Laser-assisted direct-joining of carbon fibre reinforced plastic with thermosetting matrix to polycarbonate sheets. (1st September 2017) - Lambiase, F.; Genna, S.; Leone, C.; Paoletti, A.
Graphical abstract: Highlights: CFRP was joined successfully to Polycarbonate by Laser Assisted Direct Joining. During the Joining process the covering epoxy layer was expelled from the weld seam. Then, the heated and softened PC penetrates through the carbon fibers. The effective strength of optimized joints reached 8.4 MPa. Abstract: Laser-Assisted Direct Joining (LADJ) has been employed for a wide variety of materials including metals, thermoplastics and reinforced thermoplastics. The feasibility of Laser-Assisted Direct Joining (LADJ) of Carbon Fibre Reinforced Polymer (CFRP) with thermosetting matrix to polycarbonate sheets is investigated in this work. The process was performed by means of a high-power diode laser with a maximum power of 200 W. Experimental tests were carried out by varying the main process conditions including the laser power and scanning speed. Morphological analysis using Optical and Scanning Electron Microscopy (SEM) as well as mechanical characterization of the welds were performed to understand the influence of the processing conditions on the weld quality, defects, and strength. Preliminary results have been encouraging: the process consists in removing the exterior epoxy layer from the CFRP and the adhesion of the carbon fibres to the PC. According to the achieved findings, the mechanical strength of the welds was highly affected by the Linear Energy Density (LE): low values of LE resulted in poor adhesion of the polycarbonate through the carbon fibres, which led to poor mechanical fastening and adhesion. On the other hand, processing conditions leading to excessive values of LE resulted in considerable damage of the composite matrix (the epoxy resin underlying the exposed carbon-fibre layer) and formation of bubbles on the PC substrate, which produced a dramatic reduction of the mechanical behaviour of the welds. The apparent shear strength, calculated as the ultimate shear force by the effective adhesion area was 8.4 MPa.